Effects of cysteine addition to low-fishmeal diets on the growth, anti-oxidative stress, intestine immunity, and Streptococcus agalactiae resistance in juvenile golden pompano (Trachinotus ovatus) - Liu, Jia-Xing; Zhu, Ke-Cheng; Guo, Hua-Yang; Liu, Bao-Suo; Zhang, Nan; Zhang, Dian-Chang (Frontiers in Immunology, 2022)
As the precursor of taurine, cysteine serves physiological functions, such as anti-oxidative stress and immune improvement. Investigation of cysteine and its derivatives has made positive progress in avian and mammalian species, yet the study and application of cysteine in aquatic animals are relatively rare. Therefore, we evaluated the effects of supplementing a low-fishmeal diet with various levels of cysteine on the growth, antioxidant capacity, intestine immunity, and resistance against Streptococcus agalactiae of the juvenile golden pompano (Trachinotus ovatus). According to our study, exogenous supplementation with 0.6-1.2 % cysteine greatly increased the final body weight (FBW) and specific growth rate (SGR) of golden pompano compared to the control group. Under the present conditions, the optimum dietary cysteine supplementation level for golden pompano was 0.91% based on the polynomial regression analysis of SGR. Meanwhile, we found that the Nrf2/Keap1/HO-1 signaling pathway was notably upregulated with the increase of exogenous cysteine, which increased antioxidant enzyme activity in serum and gene expression in the intestine and reduced the level of reactive oxygen species (ROS) in the serum of golden pompano. In addition, morphological analysis of the midgut demonstrated that exogenous cysteine improved muscle thickness and villi length, which suggested that the physical barrier of the intestine was greatly strengthened by cysteine. Moreover, cysteine increased the diversity and relative abundance of the intestinal flora of golden pompano. Cysteine suppressed intestinal NF-κB/IKK/IκB signaling and pro-inflammatory cytokine mRNA levels. Conversely, intestinal anti-inflammatory cytokine gene expression and serum immune parameters were upregulated with the supplementary volume of cysteine and improved intestine immunity. Further, exogenous cysteine supplementation greatly reduced the mortality rate of golden pompano challenged with S. agalactiae. In general, our findings provide more valuable information and new insights into the rational use of cysteine in the culture of healthy aquatic animals.